Hubungan Pengetahuan Ibu Post-Partum Dengan Keberhasilan Menyusui Di RSUD Leuwiliang Tahun 2021: The Relationship of Post-Partum Mother's Knowledge with Breastfeeding Success at Leuwiliang Hospital in 2021 - Nurhasanah, Neng Sri (Dohara POAJ, 2022)
Introduction: Breast milk is the main nutrition for babies aged 0-6 months, to ensure that babies get nutrients from breast milk, the mother's knowledge will greatly help to breastfeed success from the first day of birth. This study aims to determine the relationship between a mother's knowledge and breastfeeding success at Leuwiliang Hospital, Bogor in 2021. Methods: This study used a descriptive correlation design with a cross-sectional approach. The number of samples in this study is 78 breastfeeding mothers with a questionnaire instrument. Results: The results of the validity test of r results > from r data (0,444) Data analysis using the chi-square test with a degree of significance = 0.05 From the analysis results obtained p-value (0,001). Discussion: Statistical test with chi-square test obtained p-value = 0,001 < = 0,05 which indicates Ha is accepted, meaning that there is a very significant relationship between Mother's Knowledge and Breastfeeding Success at Leuwiliang Hospital in Bogor in 2021.